Segmental dynamics in hybrid polymer/POSS nanomaterials. (January 2016) - Raftopoulos, Konstantinos N.; Pielichowski, Krzysztof
Abstract: Of the many nanomaterials available today, polyhedral oligomeric silsesquioxanes (POSS) are in a class of their own as they hold the capability to combine unique reactive inorganic–organic hybrid chemical compositions with nano-sized dimensionally stable cage structures. Depending on the structure and reactivity of their vertex groups, POSS may be blended in a polymer matrix, grafted as side chains, lie on the main macromolecular contour or even act as large, multifunctional chemical crosslinks. POSS is known to influence polymer segmental dynamics with several accelerating or decelerating mechanisms, that often lead to a significant decrease or increase of the glass transition temperature ( T g ), respectively. This review explores these mechanisms with respect to the chemical nature of the organic substituents and the resulting particle–polymer interactions; the synthesis route, the chain topology, and the degree of dispersion. T g vs content data are compiled from the primary literature in a series of comparative graphs. It will be shown that the dependence of T g on the composition of the POSS nanomaterials can be often discussed and considered in terms similar to those used for polymer blends and copolymers.